Corporate restructuring, downsizing and managerial compensation - Ulrike Graßhoff; Joachim Schwalbach (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
There is common consensus that managerial compensation is strongly tied to firm size and much less so to financial performance. One suspects that observed restructuring and downsizing in corporations in recent years may have an effect on these results. Based on multi-task theoretical considerations, our evidence for German industrial firms shows that pay for firm size elasticities decrease only for large firms as they change their strategy from growth to downsizing strategies. Furthermore, pay for performance elasticities are contrary to predictions of agency theory. Both results provide further support to the common belief that compensation contracts in public corporations seem imperfectly tied to firm performance and managers' tasks.
urn:nbn:de:kobv:11-10056793
Keywords: 330